Physicochemical and Luminescent Properties of Copolymers Composed of Three Monomers: Polythiophenes Based on 3-Hexylthiophene and 3,4-Ethylenedioxythiophene - Marco Antonio Ramírez-Gómez; Karla Karina Guzmán-Rabadán; Edgar González-Juárez; Marisol Güizado-Rodríguez; Gabriel Ramos-Ortiz; Jorge Enrique Alba-Rosales; Huehueteotl Panzo-Medrano; Victor Barba; Mario Rodríguez; José Luis Maldonado; Miguel Ángel Basurto-Pensado (International Journal of Polymer Science)
The chemical synthesis and physicochemical and luminescent characterizations of polymers based on 3-HT, EDOT, and 2,2′-(9,9-dioctyl-9H-fluorene-2,7-diyl) bisthiophene (fluorene) or (E)-2-(ethyl(4-((4-nitrophenyl)diazenyl)phenyl)amino)ethyl 2-(thiophen-3-yl)acetate (TDR1) are reported. The fluorene unit was bound to the conjugate backbone, while the Disperse Red 1 (DR1) chromophore was present as a pendant group. Characterizations by 1H NMR, FT-IR, DSC-TGA, GPC, UV-vis, cyclic voltammetry, fluorescence quantum yield, excited state lifetime, and two-photon absorption cross-section were carried out. These polymers combined the physicochemical properties of EDOT and 3-HT, such as high electron density, high charge mobility, low oxidation potential, and good processability. The optical properties of these copolymers were highly dependent on the presence of EDOT, the molecular weight, and the regioregularity rather than the presence of the third component (fluorene or TDR1). The good nonlinear absorption and luminescent properties exhibited by these copolymers were exploited to fabricate nanoparticles used as fluorescent tags for the imaging of microstructures.